Exchange rate intervention in an agent based model - Jón Áskell Þorbjarnarson 1993- (2018)
Official intervention in the exchange rate market is the central bank practice of buying and selling currency in order to achieve some economic policy goal. These interventions are a fact for many currencies, both large and small. This paper investigates these interventions in a heterogeneous agents based model of foreign exchange trading. We look at rules based strategies of intervention that a central bank could implement based both on activity in the foreign exchange market and through interest rate policy. We find that a so called leaning against the wind policy is superior to target zones or changes in interest rate policy. The model has limited applicability in Iceland at the present time due to regulations that prevent speculative currency trading. It is however likely that these restrictions will be lifted in due time. Opinber íhlutun á gjaldeyrismarkaði kallast það þegar seðlabankar kaupa eða selja gjaldeyri til að stuðla að stefnu sinni. Íhlutanir af þessari gerð eiga sér stað á mörgum mynstvæðum, bæði stórum og smáum. Í þessari ritgerð skoðum við inngrip á gjaldeyrismarkaði í fulltrúalíkani af gjaldeyrismarkaðnum. Við skoðum áhrif reglubundinna inngripa seðlabanka sem byggja á gengishreyfingum og vaxtastigi. Niðurstöðurnar eru á þann veg að inngrip geti haft sveiflujafnandi áhrif séu þau af þeirri gerð sem nefnt hefur verið að halla upp í vindinn frekar en að reynt sé að halda gengi innan ákveðinna marka eða beita vaxtaákvörðunum. Líkanið hefur takmarkað notagildi við íslenskar aðstæður um þessar mundir sökum hafta á spákaupmennsku á gjaldeyrismarkaði. Ekki er þó ólíklegt að þeim höftum verði aflétt þegar fram líða stundir.